IDENTIFIKASI PARASIT PADA IKAN TONGKOL (Euthynnus affinis) DI TEMPAT PELELANGAN IKAN LHOKNGA ACEH BESAR (Identification of Parasites in Mackerel (Euthynnus affinis) at Fish Auction in Lhoknga Aceh Besar) - Nurul Hidayati; Muttaqien Bakri; Rusli Rusli; Yudha Fahrimal; Muhammad Hambal; Razali Daud (Jurnal Medika Veterinaria, 2016)
The objective of this study was to identify parasites that infect mackerel fish (Euthynnus affinis) at fish auction in Lhoknga, Aceh Besar. Fifteen mackerel fish collected from fish auction in Lhoknga were examined at Parasitology Laboratory, Faculty of Veterinary Medicine Syiah Kuala University Banda Aceh to observe the presence of ectoparasites and endoparasites. The ectoparasite examination was conducted by observation of the external body part and then examined under microscope, while endoparasite examination conducted by observation of inner surface of digestive tract. The data showed that two types parasites infested the mackerel fish at fish auction in Lhoknga were Anisakis simplex and Neobenedia melleni. A total of 87% mackerel fish was infested with A. simplex and 7% was infested with N. melleni.